Formulation and Antibacterial Activity Tests of Nanoemulsion Gel Black Cumin (Nigella Sativa L.) Ethanol Extract - L, Syahfitri E; J, Reveny; M, Nainggolan (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: Black cumin (Nigella sativa L.) is an herbal plant that has the chemical content of essential oil and pharmacological effect as a broad-spectrum antibacterial namely thymoquinone (TQ). This research was carried out by making ethanol extract of black cumin, formulating it into nanoemulsion gel and testing the antibacterial activity against pathogenic bacteria in the skin. Methods: Black cumin seeds macerated with 80% alcohol and concentrated with a rotary evaporator. Black cumin ethanol extract is formulated into nanoemulsion gel using spontaneous emulsification with concentrations of 3%, 5% and 7%. The preparation is stored and evaluated for 12 weeks at room temperature. Evaluation of preparation quality includes organoleptic, viscosity, particle size, centrifugation and cycling test. Antibacterial activity test of nanoemulsion gel of black cumin ethanol extract was carried out by cup-plate technique using Staphylococcus aureus, Staphylococcus epidermidis dan Propionibacterium acne. Results: the extract yield was 18,37% w/w. All formulas were stable during 12 weeks storage, viscosity 2850-3750 mPa.s, particle size around 45,85-419,78 nm, centrifugation results and cycling tests showed no sedimentation and phase separations, so it were said to be physically stable. The results of the antibacterial activity test showed the value of minimum inhibitory concentration (MIC) of Staphylococcus aureus bacteria in F1, F2 and F3 respectively 7,83; 8,93 and 10,00 mm, Staphylococcus epidermidis bacteria 6,63; 7,67 and 8,43 mm, Propionibacterium acne bacteria 6,43; 7,47 and 7,83 mm. Conclusion: The results of the study concluded that nanoemulsion gel of black cumin ethanol extract with a concentration of 7% is the best formula because it is stable during storage, has the greatest antibacterial activity against pathogenic bacteria in the skin.